MODELING OF ROAD TRAFFIC CRASH COUNTERMEASURES IN OGUN STATE (Nigerian Journal of Technology, 2019)
Road traffic crash is a global concern and Nigeria is not left behind. In 2016, 387 Road Traffic Crashes were recorded in Ogun State out of which 279 persons were killed and 1366 were injured The aim of the study is to develop a model for describing road traffic crash countermeasures in Ogun State. Questionnaire on existing safety measures which involved 8 questions were administered to 240 respondents drawn from six of the twenty LGAs of Ogun State. A multivariate regression model was developed for describing road traffic crash countermeasures. The model revealed that all the countermeasures contributed positively to the overall level of road traffic crash control. Maintenance of road network with positive regression parameter of 1.0610 contributed most to the overall reduction in road traffic crash in the study area. It is therefore concluded that more attention should be channeled towards road maintenance and rehabilitation in Ogun State. http://dx.doi.org/10.4314/njt.v38i4.1